Pelatihan Pembuatan Pupuk Kompos dari Sampah Organik Menggunakan Compost Bag untuk Mendukung Program Kampung Iklim (Proklim) di Desa Ngrawan Kecamatan Getasan Kabupaten Semarang - Hanif, Miftahudin; Melati, Dinda; Paranti, Lesa; Lungguh, Lungguh (Jurnal Bina Desa, 2025)
Organic waste is still a problem in Ngrawan Village, Getasan Regency, affecting the surrounding environment. The existence of these environmental problems requires efforts and solutions to overcome them. This service aims to provide knowledge about making compost using compost bags. The method used in implementing this service is using socialization, direct demonstrations, and assistance in making compost fertilizer every week. The benefits of this activity are optimizing the climate village program in Ngrawan Village, providing an understanding of environmental problems in Ngrawan Village, and mitigation efforts, as well as empowering the local economy by making compost independently. The results obtained are that the community knows about environmental problems in Ngrawan Village and efforts to mitigate and overcome them and the products produced from this community service activity are mature compost fertilizer that has been successfully made by the community, knowledge of the use of compost bags and materials that can be used as educational facilities for visitors to Ngrawan village. The conclusion is that in dealing with environmental problems and waste management, awareness is needed from an early age by the younger generation in Ngrawan Village.